Suicide and social justice : new perspectives on the politics of suicide and suicide prevention - Button, Mark E.; Marsh, Ian, 1967- (New York, NY : Routledge, 2020)
Suicide and Social Justice unites diverse scholarly and social justice perspectives on the international problem of suicide and suicidal behavior. With a focus on social justice, the book seeks to understand the complex interactions between individual and group experiences with suicidality and various social pathologies, including inequality, intergenerational poverty, racism, sexism, and homophobia. Chapters investigate the underlying and often overlooked connections that link rising rates and disproportionate concentrations of suicide within specific populations to wider social, political, and economic conditions. This edited volume brings diverse scholarly and social justice perspectives to bear on the problem of suicide and suicidal behavior, equipping researchers and practitioners with the knowledge they need to fundamentally rethink suicide and suicide prevention.
OCLC-licensed vendor bibliographic record.
Keywords: Suicide; Suicide -- Prevention; Suicidal behavior -- Social aspects; POLITICAL SCIENCE / Public Policy / Social Policy; PSYCHOLOGY / Mental Health; PSYCHOLOGY / Suicide